A newborn with Timothy syndrome and torsades de pointes - Lucas, Eliane; Bravo-Valenzuela, Nathalie; Loureiro, Talita; Madruga, Anette; Sacramento, Lívia Maria; Lima, Camille; Gonçalves, Sérgio (Prenatal Cardiology, 2022)
Timothy syndrome (TS) is a rare multisystem disease with a characterized association of long QT syndrome (LQTS) type-8 with congenital cardiac and extracardiac malformations (neurological and dysmorphic facial features, syndactyly). It is caused by heterozygous mutations in the CACNA 1C gene, which participates in decoding the calcium channels. In this study, we describe a case of TS with systemic phenotypic characteristics associated with a long QT interval on the electrocardiogram. The LQTS predisposes to a characteristic life-threatening ventricular arrhythmia known as torsades de pointes or “twisting of the points”. In this scenario, the authors describe the main clinical characteristics in a case of TS focusing on improving the ability of early diagnosis and on better management of LTQS type-8.